KNOWLEDGE RELATIONSHIP WITH MOTHER OF CONDUCT GIVING FOOD COACH ASI (MP-ASI) IN THE VILLAGE KEMUNING, NGARGOYOSO, KARANGANYAR - Chintami Permatasari (Gaster, 2016)
Food Companion mother's milk (breast milk) is a food or drink other than breast milk contains nutrients given to infant feeding during the period of transition, namely when food or drink is supplied with breastfeeding. Preliminary studies conducted in Desa Kemuning, Ngargoyoso showed 70% of mothers have give breast milk before the baby is 6 months old and 30% of mothers who give complementary feeding on time. 70% of mothers who breast milk before the age of 6 months had less knowledge about the provision of complementary feeding. Objective: To determine the relationship between the mother's knowledge by giving complementary feeding behavior. Methods: The study was observational analytic with cross sectional design. The subjects were mothers of infants aged 0-12 months as many as 76 respondents with a sampling technique uses accidental sampling. Data analysis used was Spearman Rank. Results: Most of the mothers' knowledge of breast milk is low (69.7%) and the majority of the provision of complementary feeding behavior less (78.9%). Spearman Rank test result values ​​obtained Zhitung> Ztabel (9.13> 1.96) p value 0.336 so that Ho refused and Ha accepted. Conclusion: There is a relationship between the mother's knowledge by giving complementary feeding behavior.